1981
DOI: 10.1002/j.1537-2197.1981.tb06350.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Priorities With Respect to Growth and Mineral Uptake in Roots of Hordeum, Triticum and Lycopersicon

Abstract: Reduction in the supply of photosynthate to the roots of tomato, barley, and wheat plants was achieved indirectly by lowering the intensity of sunlight striking the foliage of test plants. The decrease in sugar and starch concentrations in the roots was verified by appropriate extraction and colorimetric analysis, and a corresponding reduction in the total respiratory rate of the roots was confirmed using an oxygen tension monitor. Other processes measured directly include the rate of uptake of potassium, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Indeed, the absorption rates of nutrients have been found to be lower when the energy supply of the roots is limited (CRAPO & KETELLAP-PER 1981, HANISCH TEN CATE & BRETELER 1981, KOSTER 1973, but in all those experiments it was always measured in high light intensity plants in which the energy supply of the roots was limited artificially, for example by moving the plants into shade. And since CRAPO & KETELLAPPER (1981) found that root growth was restricted much more than nutrient (potassium) absorption by low energy supply, it seems probable that these results do not apply unconditionally for plants adapted to a low energy supply. It can be concluded that plants react to low nitrate supply mainly by means of morphogenetic adaptations and they maintain a reasonable organic nitrogen content.…”
Section: Growth and Morphogenesismentioning
confidence: 81%
“…Indeed, the absorption rates of nutrients have been found to be lower when the energy supply of the roots is limited (CRAPO & KETELLAP-PER 1981, HANISCH TEN CATE & BRETELER 1981, KOSTER 1973, but in all those experiments it was always measured in high light intensity plants in which the energy supply of the roots was limited artificially, for example by moving the plants into shade. And since CRAPO & KETELLAPPER (1981) found that root growth was restricted much more than nutrient (potassium) absorption by low energy supply, it seems probable that these results do not apply unconditionally for plants adapted to a low energy supply. It can be concluded that plants react to low nitrate supply mainly by means of morphogenetic adaptations and they maintain a reasonable organic nitrogen content.…”
Section: Growth and Morphogenesismentioning
confidence: 81%
“…The exterior leaves of grape shoots in the middle of the canopy contain more sugars than the interior or lower leaves (Sytnik et al 1978). In general, it has been agreed that insufficiency of light, low temperatures and disturbed water supply reduce the content of carbohydrates in plants (Crapo and Ketellaper 1981;Geiger and Conti 1983) and bring about changes in the anatomic properties of the plants (Kappel and Flore 1983). Also, the decrease of growth induced by air pollution may be due to changes in carbon allocation in plants as recorded for Populus tremuloides by Coleman et al (1995Coleman et al ( , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…In the shrub-steppe vegetation of the Great Basin, shading by larger shrubs can be appreciable, especially when solar angles are lower as in early spring and late fall (Caldwell et al 1981;West 1988). In the short term, direct effects of shading can lead to reductions in root growth, carbohydrate content, respiration, and ion uptake (Crapo and Ketellapper 1981;Jackson and Caldwell 1992). In field experiments, shading has been shown to reduce root proliferation of A. desertorum in enriched nutrient patches (Bilbrough and Caldwell 1995) and can lead to lower root P uptake capacity in enriched soil patches (Jackson and Caldwell 1992).…”
Section: Introductionmentioning
confidence: 99%